Radiosensitivity and in vitro mutagenesis in African accessions of cassava, Manihot esculenta Crantz - Owoseni, O.; Okwaro, H.; Afza, R.; Bado, S.; Dixon, A.; Mba, C. (2006)
Induced mutagenesis holds promise for the subtle manipulation of traits of interest in crop plants. For a vegetatively propagated crop like cassava with severe constraints posed on its genetic improvement by inherent biological systems, the adoption of this methodology seems even the more appealing. However, there is scant information on protocols for inducing mutations in this crop. We present in this report the preliminary data on the determination of radiosensitivities for some African cassava accessions. The optimal doses of gamma ray irradiation varied from as low 12 Gy to 25 Gy. The probable implication of genotypic variation in response to gamma irradiation as was found in this study buttresses the need to carry out this larger scale study in order to avail cassava scientists intending to adopt induced mutagenesis of requisite information in this regard. A modified in vitro culture medium, half strength MS without growth hormones, was also shown to greatly enhance the growth of the plantlets without producing callus.